Bioefficacy of different insecticides against blister beetle Mylabris phalerata (Pallas) on pigeonpea (SAARC Journal of Agriculture, 2017)
The experiment was accomplished to evaluate the bioefficacy of different insecticides against Mylabris phalerata (Pallas) on pigeonpea. The experiment consisted of seven treatments viz., bifenthrin 62 g a.i. ha-1, lambda-cyhalothrin 24 g a.i. ha-1 (encapsulated with polymers; Matadore), chlorpyriphos 310 g a.i. ha-1+ cypermethrin 31 g a.i. ha-1, cypermethrin 62 g a.i. ha-1, neem oil 1500 ppm, permethrin 154 g a.i. ha-1, chloropyriphos 173 g a.i. ha-1 compared with untreated (control). The sixth day after each spray, minimum population abundance of M. phalerata and maximum percent efficacy in reducing their population was obtained from bifenthrin which was at par with lambda-cyhalothrin, cypermethrin, chlorpyriphos+ cypermethrin and permethrin and all these were significantly effective over chloropyriphos, neem oil and control plots. On the tenth day after each spray, minimum population abundance and highest per cent efficacy were obtained from bifenthrin which was at par with lambda-cyhalothrin and both these treatments were significantly superior over rest of the treatments. The maximum productivity was observed with bifenthrin, while highest net return per rupee investment was obtained from lambda-cyhalothrin treatment. The results explicitly show that out of all treatments, Lambda-cyhalothrin was effective and imposing lucrative against M. phalerata and thereby minimized the yield loss. Three sprays of lambda-cyhalothrin and bifenthrin with an interchange at ten days interval will be effectual and lucrative against M. phalerata in short duration pigeonpea crop.SAARC J. Agri., 15(1): 55-65 (2017)